PENINGKATAN PEMAHAMAN MASYARAKAT DESA WONOSALAM KABUPATEN DEMAK MENGENAI DASAR HUKUM DAN PENYELESAIAN SENGKETA KOPERASI SYARIAH - Dian Rosita; Endang Setyowati (CV. Denasya Smart Publisher, 2024)
Sharia Cooperatives are a form of cooperative that has principles, objectives and business activities based on Islamic Sharia, namely the Al-Qur'an and Assunah. The legal basis for establishing a sharia cooperative itself includes the following: Law of the Republic of Indonesia No. 25 of 1992 concerning Cooperatives, PP No. 9 of 1995 concerning the Implementation of Savings and Loans Business Activities by Cooperatives, Minister of Cooperatives and SMEs Regulation No. 11/M.KUKM/XII/2017 concerning Implementation of Savings and Loans and Sharia Financing Business Activities by Cooperatives, Minister of Cooperatives and SMEs Regulation No. 35.2/Per/M.KUKM/X/2007 Concerning Guidelines. Cooperative Management Operational Standards. The problem that often arises in the practice of sharia cooperatives is the emergence of problematic financing or bad credit. Dispute resolution can be resolved in two ways, namely dispute resolution in court or outside court. Due to the negative impact of the emergence of problematic financing, it is necessary for the Community Service Team (PkM) to organize outreach and counseling with the theme